Boru ni Raja: Agency and Social Transformation of Toba Batak Women in Inclusive Rural Development in Silindung, North Tapanuli - Firmando, Harisan Boni; Teresia Simbolon, Elvri; Lumbantobing, Roida (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2025)
This study examines how Boru ni Raja (women of royal descent) in Toba Batak society exercise agency to drive inclusive rural development in Silindung, North Tapanuli, Indonesia. Grounded in the social action theory of Max Weber and the structuration theory of Anthony Giddens, the study fills a crucial knowledge vacuum regarding how indigenous women navigate patriarchal systems through culturally embedded strategies. Using a 16-month multi-site ethnography (2023–2024), comprising 45 informants' interviews, document analysis, and participatory observation, the study reveals four key strategies: (1) leveraging cultural capital (82% efficacy), (2) building transgenerational networks (68%), (3) innovating local economies (57%), and (4) negotiating political spaces (39%). Findings demonstrate that Boru ni Raja reinterpret traditional values like Dalihan Na Tolu (kinship philosophy) and hasangapon (dignity) to legitimize leadership, resulting in a 320% increase in women’s institutional representation (2020–2023) and a 45% rise in average income. Despite resistance from male elites (60% of cases), their incremental approach transforms patrilineal structures without overt conflict, highlighting the potential of indigenous knowledge in fostering hybrid modernity. The study contributes to sociological debates on gender, development, and cultural change by theorizing subaltern agency in rigid hierarchies. Practical implications emphasize culturally sensitive empowerment programs for traditional societies.